Defending gentrification as a valid collective conception: Utilizing the metanarrative of "Suburbia" as a common axis for the diversity of middle-class reurbanization projects - Oliver, Miguel de (Urban Affairs Review)
A long-standing problem in gentrification research is the increasingly diverse array of interests and agendas in the renewal of the inner city; their diversity has frustrated many scholars with respect to the collective characterization and comprehension of the phenomenon. Consequently, others have questioned the validity of the term (3z(Bgentrification(3y (Bitself. This article contends that gentrification is a phenomenon that merits being collectively identified. The relocation of the middle class to the urban core has been portrayed in terms of actors and agendas, places and processes. These criteria have long since been inadequate to collectively rationalize gentrification in anything other than strictly spatial terms. But when suburbia is perceived as a metanarrative, the collective character of gentrification becomes evident; for it is the process of the metanarrative$1 (Bs systemic erosion in the postmodern era that serves the long-standing desire to find an operant commonality to gentrification$1 (Bs apparent lack of coherence. - Reproduceds